Radiocarbon ages of sediment core samples from the Bay of Bengal - Hein, Christopher; Eglinton, Timothy; Haghipour, Negar; Galy, Valier (IEDA: EarthChem Library, 2020)
Abstract: This dataset presents results from AMS-radiocarbon dating of planktonic foraminifera from sediment core samples collected during cruise SO93 on R/V Sonne in the Bay of Bengal. These data are used to refine age models for the sediment cores. Other Description: Hein, C.J., Usman, M., Eglinton, T.I., Haghipour, N., Galy, V.V., in press (2020), "Millennial-scale hydroclimate control of tropical soil carbon storage." Nature.